The Bioerosion of Submerged Archeological Artifacts in the Mediterranean Sea: An Overview - Sacco Perasso, Carlotta; Antonelli, Federica; Calcinai, Barbara; Casoli, Edoardo; Gravina, Maria Flavia; Ricci, Sandra (Frontiers in Marine Science, 2022)
Bioerosion is the destruction of hard substrates resulting from biological activity, and plays a relevant role in the ecological interactions and coastal dynamics processes. Several organisms have evolved structures and behaviors allowing them to perforate biotic and abiotic surfaces, transforming hard surfaces into particles, and contributing significantly to sediment production in the coastal and marine environment. Due to the large geographical diffusion of marine borers, bioerosion is relevant in many scientific and applied fields of interest. Most bioerosion studies have hitherto been conducted in tropical areas, where borers are a critical component of coral reef destruction. Comparatively, little information is available for the bioerosion of submerged archeological heritage. This review focuses on the bioerosion of archeological calcareous artifacts in the Mediterranean Sea, summarizing studies concerning the colonization of statues, shipwrecks, cargo, and the remains of submerged cities. The paper includes the first comprehensive listing of the archeological sites in the Mediterranean Sea where bioerosion has been assessed. The diversity of boring organisms affecting marine archeological remains and their boring patterns, the various types of bored materials, and the severity of the damage caused to heritage artifacts are also included. Both microborers (algae, fungi, and cyanobacteria) and macroborers (sponges, bivalves, polychaetes, sipunculids, and echinoids) are considered, and their roles in the structuring of endolithic assemblages are also covered. The experimental techniques currently employed to analyze bioerosion traces, helping to identify particular species and ichnospecies and their ecological dynamics, are also considered. Finally, a discussion of the current strategies proposed for the in situ protection and conservation of Underwater Cultural Heritage is provided.